Topology of electron density of cadmium telluride determined from relief and contour plots - Othman, A.P.; Gopir, G.A. (Universiti Kebangsaan Malaysia, 2013)
The topology of the electron density yields a faithful and a reliable mapping of the concepts of atoms, molecular structure, bonds and structure, besides providing the basis for a theory of structural stability. In quantum mechanics and in particular quantum chemistry, the electron density is a measure of the probability of an electron occupying an infinitesimal element of space surrounding any given point. Contour plots of electron density distribution of cadmiun telluride (CdTe) were obtained using the density functional theory (DFT) method and were used as the basis to qualitatively study the bond, structure and stability of the molecule when it is in bulk. We looked at the way the electron density, ρ of CdTe defines the gradient field and hence the bonding type. We identified the bond paths that coincide with the contours of electron sharing. These bond paths indicated that the molecule was slightly covalent. Our topological analysis led us to conclude that CdTe was an n-type semiconductor with covalent bond and slight ionic character.